2015
DOI: 10.1098/rspb.2014.2562
|View full text |Cite
|
Sign up to set email alerts
|

Odourant dominance in olfactory mixture processing: what makes a strong odourant?

Abstract: The question of how animals process stimulus mixtures remains controversial as opposing views propose that mixtures are processed analytically, as the sum of their elements, or holistically, as unique entities different from their elements. Overshadowing is a widespread phenomenon that can help decide between these alternatives. In overshadowing, an individual trained with a binary mixture learns one element better at the expense of the other. Although element salience (learning success) has been suggested as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 51 publications
(54 reference statements)
5
22
0
Order By: Relevance
“…More general interactions between odorants and receptors can be easily added to our model, at the cost of additional parameters. For example, we showed that the nonlinearities implied by just competitive exclusion and facilitation are sufficient to produce diverse e ects that have been previously reported in the perception of odor mixtures including synergy (17), overshadowing (16), suppression (31) and inhibition (29). These e ects were thought to have a neural origin, but our results suggest that they may be driven partly by the biophysics of receptors.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…More general interactions between odorants and receptors can be easily added to our model, at the cost of additional parameters. For example, we showed that the nonlinearities implied by just competitive exclusion and facilitation are sufficient to produce diverse e ects that have been previously reported in the perception of odor mixtures including synergy (17), overshadowing (16), suppression (31) and inhibition (29). These e ects were thought to have a neural origin, but our results suggest that they may be driven partly by the biophysics of receptors.…”
Section: Discussionsupporting
confidence: 68%
“…Our approach is rooted in basic biophysics. For example, the extended models consider consequences of known phenomena like receptors with multiple binding sites, facilitation by already bound odorants, non-competitive inhibition, and heterodimerization of odorant molecules in mixture, and predict e ects such as synergy, antagonism (15) and overshadowing (16) in receptor responses. Such phenomena are reported in studies of human olfactory perception (17), but their origin is unknown.…”
mentioning
confidence: 99%
“…Third, food sources and the environment constantly undergo changes in odorant concentrations over the course of a day. Moreover, for honeybees, some odorants are more salient and distinct in a mixture than others (Reinhard et al, 2010;Schubert et al, 2015). Thus the question arises, how does a honeybee filter the relevant odor cues from an abundance of an ever-changing environmental odor background?…”
Section: Discussionmentioning
confidence: 99%
“…When two odours are presented simultaneously to honeybees, one of these odours can potentially overshadow or block the other so that the bees only respond to the more salient odour (Smith 1998;Guerrieri et al 2005;Reinhard et al 2010;Schubert et al 2015). This effect could explain the decrease in aggression induced by floral compounds such as PhE or Lol when presented with IAA.…”
Section: Iaa Is Not Masked By Floral Compounds Blocking Aggressionmentioning
confidence: 98%
“…Indeed, IAA seems to mask the plant odour, which is not surprising considering that IAA is present at much higher concentrations in the mixture than the plant odour (10% vs 0.075%, Table 1). Bees conditioned to odour mixtures respond more to a dominant component in the mixture (Reinhard et al 2010;Schubert et al 2015). Based on this finding, bees trained to IAA+PhE or IAA+Pr should respond more to IAA and less to the plant odour given the concentration differences of these odorants.…”
Section: Iaa Is Not Masked By Floral Compounds Blocking Aggressionmentioning
confidence: 99%